Design of Data Warehouse for University Library using Kimball and Ross 9 Steps Methodology - Darma Kotama, I Nyoman; Oka Kessawa Adnyana, Anak Agung Gede; Saputra, Komang Oka (International Journal of Engineering and Emerging Technology, 2019)
Udayana University has a library that purposed to serve all the student and lecturer needs in Post graduate program. To help achieve University goals to be a world class university, improvement of library management and assessment of its value and function is needed. Data Warehouse concept is a long proven solution that exist to help the upper management know the state of the institution through its own data. Effective design of Data Warehouse can help the management of institution to decide critical evaluation for its institution. On past research Kimball & Ross propose a technique to build an effective design of Data Warehouse named “9 Steps Methodology”. This paper is aiming to build an effective design of Udayana Postgraduate Library Data Warehouse using Kimbal & Ross Methodology. We hope by this blueprint we can contribute to the future of the library by providing additional choice of Data Warehouse Design. After we follow through all the 9 steps and using past 3 years data of the library, we successfully designed model of Data Warehouse that consist of 8 dimension tables and 9 facts tables